Cellulose full-biodegradable super-tough tableware
By using components such as polycaprolactone, cellulose acetate, modified reed cellulose, and spraying the hydrophobic layer of components such as beeswax-loaded nanosilicon dioxide on the surface, the existing problems of poor toughness, biodegradability and hydrophobic properties of full biodegradable tableware are solved, and cellulose full biodegradable ultra-tough tableware with high toughness, waterproofness and biodegradability are achieved.
Patent Information
- Application Number
- CN202411794847.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-28
AI Technical Summary
The toughness, biodegradability and hydrophobic properties of existing fully biodegradable tableware are poor.
Polycaprolactone, cellulose acetate, modified reed cellulose, pentaerythritol stearate, talc, antioxidants and beeswax-loaded nanosilica were prepared by melt blending granulation, injection molding and spraying hydrophobic layers.
It significantly improves the toughness, waterproofness and biodegradability of the tableware, forms an excellent hydrophobic layer, and enhances the overall performance of the tableware.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of tableware preparation, and in particular relates to cellulose fully biodegradable super-tough tableware. Background Art
[0002] As people's awareness of environmental protection increases, the demand for biodegradable materials continues to increase. Cellulose, as a natural degradable material, has good biocompatibility and environmental friendliness, so it is widely used in the preparation of biodegradable tableware. However, traditional cellulose tableware often has problems such as low strength and easy water absorption and swelling, which limits its widespread use in practical applications.
[0003] Patent CN 114703692 A discloses a straw-based fully biodegradable tableware production process, the steps are: cutting straw; vibrating screening to remove impurities; crushing straw to form fibrous materials; adding water to soften fibrous materials; hydraulically crushing fibrous materials to form floccules; feeding floccules into a straw decomposer to enhance the mechanical properties of fibers; feeding floccules, bone glue, xanthan gum, light calcium carbonate, talcum powder, carbonate and clean water into a mixer to prepare cellulose slurry; hot pressing cellulose slurry to prepare tableware blanks; cooling and drying tableware blanks; demolding tableware blanks to form rough tableware products; washing rough tableware products; cutting edges of rough tableware products to form semi-finished tableware products; waterproofing and oil-releasing semi-finished tableware products; disinfecting semi-finished tableware products to form finished tableware products; sampling finished tableware products and storing them only after all indicators are qualified. The production process of this invention does not require the addition of toxic chemical additives, and there is no sewage discharge during the entire process, which has the characteristics of energy saving and environmental protection, but the toughness, biodegradability and hydrophobicity of the tableware obtained by this process need to be improved. Summary of the invention
[0004] The purpose of the present invention is to provide cellulose fully biodegradable and ultra-tough tableware, so as to solve the technical problems of poor toughness, biodegradability and hydrophobicity of fully biodegradable tableware in the prior art.
[0005] In order to achieve the above object, the present invention adopts the following technical solutions:
[0006] The invention provides cellulose fully biodegradable super-tough tableware, which is composed of a tableware sample embryo and a hydrophobic layer. The tableware sample embryo comprises the following components in parts by weight: 3-5 parts of polycaprolactone, 75-80 parts of cellulose acetate, 4-8 parts of modified reed cellulose, 0.5-1.0 parts of pentaerythritol stearate, 9-10 parts of talc, 0.1-0.2 parts of antioxidant 1010, and 0.2-0.3 parts of antioxidant 168; the hydrophobic layer comprises the following components in parts by weight: 0.5-1 parts of nano silicon dioxide loaded with beeswax, 0.25-0.5 parts of polydimethylsiloxane, and 0.25-0.5 parts of tetrahydrofuran.
[0007] Preferably, the method for preparing the modified reed cellulose comprises the following steps:
[0008] P1: Cut the reed into long strips, wash and air-dry them naturally, then fully crush them with a cutting grinder, sieve them to obtain reed powder, take the reed powder and wrap it with filter paper, put it in a Soxhlet extractor, add a mixed solution of toluene and ethanol, heat and extract, after the extraction is completed, take out the remaining product, vacuum filter, wash and dry it to obtain pretreated reed powder;
[0009] P2: The pretreated reed powder is placed in a round-bottom flask, and a mixed solution of potassium hydroxide and potassium permanganate is added. The round-bottom flask is first ultrasonically cleaned in an ultrasonic cleaner, and then the round-bottom flask is connected to a condensation device for extraction. After the extraction is completed, vacuum filtration, washing, and drying are performed to obtain reed crude fiber;
[0010] P3: Place the reed crude fiber in a round-bottom flask, add glacial acetic acid, place it in a constant temperature oil bath for magnetic stirring, filter, wash, and dry to obtain modified reed cellulose.
[0011] Preferably, in P1, the strip length is 3-5 cm, the sieved particle size is 80-100 mesh, the volume ratio of toluene to ethanol is 2:(0.8-1.2), the heating temperature is 80-90°C, the extraction time is 8-10h, and the drying temperature is 100-105°C.
[0012] Preferably, in P2, the dosage ratio of reed powder, potassium hydroxide and potassium permanganate is 5g:
[0013] (50-60)mL: (40-50)mL, the mass fraction of potassium hydroxide is 4wt%, the volume fraction of potassium permanganate is 0.6vt%, during the ultrasonic cleaning process, the ultrasonic frequency is 45-50kHz, the cleaning time is 20-40s, the extraction treatment temperature is 70-80℃, the extraction treatment time is 4-6h, washing to pH=7, and the drying temperature is 100-110℃; in the P3, the pH of glacial acetic acid is 3.5, and the temperature of the constant temperature oil bath is 80-90℃.
[0014] Preferably, the method for preparing the beeswax-loaded nano-silicon dioxide comprises the following steps:
[0015] S1: adding tetraethyl orthosilicate to a mixed solution of ethanol, deionized water and ammonia solution, stirring, centrifuging, washing and drying to obtain solid nano-silica particles, then ultrasonically dispersing the solid nano-silica particles in deionized water, adding an ethanol solution containing hexadecyltrimethylammonium bromide, stirring and adding anhydrous sodium carbonate, continuing to stir, heating and stirring, centrifuging, washing and drying to obtain hollow nano-silica;
[0016] S2: beeswax is added to ethanol containing hollow nano-silica, and after ultrasonic dispersion, it is placed in a vacuum environment, magnetically stirred, washed, and dried to obtain nano-silica loaded with beeswax.
[0017] Preferably, in S1, the volume ratio of tetraethyl orthosilicate, ethanol, deionized water and ammonia solution is (5-8): (70-80): (8-12): (3-3.5), the volume fraction of ammonia solution is 25vt%, the stirring time is 1-2h, the centrifugal speed is 4000-5000rpm, the drying temperature is 120-130°C, the drying time is 10-12h, and the amount of solid nano-silica particles, deionized water, hexadecyltrimethylammonium bromide, ethanol and anhydrous sodium carbonate is The ratio is (0.3-0.8) g: 90 mL: (1-1.5) g: 10 mL: (2-2.3) g, the stirring time is 1-2 h, the continued stirring time is 10-12 h, the heating temperature is 50-60 ° C, and the stirring time is 20-22 h; in S2, the amount ratio of beeswax, hollow nano-silica and ethanol is (0.6-1.2) g: (0.2-0.6) g: 40 mL, the ultrasonic dispersion time is 30-40 min, and the magnetic stirring time is 12-14 h.
[0018] Preferably, the method for preparing the fully biodegradable ultra-tough cellulose tableware comprises the following steps:
[0019] Step (1): melt-blending polycaprolactone, cellulose acetate, modified reed cellulose, pentaerythritol stearate, talc, antioxidant 1010, and antioxidant 168 to form granules, then adding the granules into a barrel of an injection molding machine, and then injecting the granules into a tableware mold, and then cooling the granules to obtain a tableware sample embryo;
[0020] Step (2): adding polydimethylsiloxane to tetrahydrofuran, dispersing it by ultrasonication to make it completely dissolved, then adding nano-silica loaded with beeswax, dispersing it by ultrasonication and continuing to stir to obtain a hydrophobic dispersion;
[0021] Step (3): The dispersion is loaded into a spray gun and sprayed evenly on the surface of the tableware sample. After the spraying is completed, the tableware sample is placed in an oven for curing to obtain cellulose fully biodegradable and ultra-tough tableware.
[0022] Preferably, in step (1), the melt blending temperature is 210°C-230°C, and the injection molding temperature is 210°C-230°C.
[0023] Preferably, in the step (2), the ultrasonic dispersion time is 15-20 min, the ultrasonic dispersion time after adding the nano-silica loaded with beeswax is 30-45 min, and the stirring time is 30-40 min; in the step (3), the air pressure of the spray gun is 0.2-0.4 MPa, and the mixture is dried in an oven.
[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0025] 1. The present invention first uses reed as a main raw material to extract reed cellulose, which is chemically modified with glacial acetic acid to obtain modified reed cellulose with excellent toughness, and then melt-blending and granulating polycaprolactone, cellulose acetate, modified reed cellulose, pentaerythritol stearate, talcum powder, antioxidant 1010, and antioxidant 168, and injection molding to obtain a tableware sample embryo, and then polydimethylsiloxane is added to tetrahydrofuran, and nano-silicon dioxide loaded with beeswax is added to prepare a hydrophobic dispersion, which is solidified on the surface of the tableware as a hydrophobic layer to form a hydrophobic layer. The tableware obtained by the method has excellent toughness, waterproofness and biodegradability.
[0026] 2. The present invention adds reeds to a mixed solution of toluene and ethanol, obtains reed powder through pretreatment, then adds potassium hydroxide and potassium permanganate, performs extraction treatment, obtains reed crude fiber, and finally places the reed crude fiber in a round-bottom flask, adds glacial acetic acid, places it in a constant temperature oil bath pot for magnetic stirring, suction filtration, washing, and drying to obtain modified reed cellulose. After a series of pretreatments such as adding toluene, ethanol, potassium hydroxide, and potassium permanganate to the reeds, the reed cellulose can be microfibrillated and more active hydroxyls are exposed, providing more reaction sites for chemical modification. The addition of glacial acetic acid causes it to undergo an esterification reaction with the active hydroxyls to form a stable structure, thereby enhancing the toughness of the modified reed cellulose. The prepared modified reed cellulose is used as the main material of tableware, which can effectively increase the toughness and biodegradability of the tableware.
[0027] 3. In the present invention, the fiber is prone to degradation during the high-temperature injection molding process, and antioxidants 1010 and 168 are added. The antioxidants can react with free radicals in the fiber to prevent the free radical chain reaction from proceeding, thereby protecting the fiber and inhibiting the degradation of cellulose. The antioxidants can also inhibit or slow down the oxidation reaction, improve the aging resistance of the textile, and extend its service life. In addition, in order to reduce production costs, talcum powder is added as an additive filler. The presence of an appropriate amount of talcum powder can also effectively fill the pores of the interface, making the fracture surface of the composite material smoother, improving the interfacial compatibility of the blending system, and making the tableware show excellent toughness. In addition, talcum powder has excellent heat resistance, and filling talcum powder can improve the thermal stability of the tableware.
[0028] 4. The nano-silica loaded with beeswax in the present invention has an excellent hydrophobic effect, which is due to the fact that the nano-silica with a hollow structure has a large specific surface area and pore volume, increases the contact area between beeswax and silica, improves the adhesion and stability of beeswax, and beeswax is a natural hydrophobic substance, and contains a large number of hydroxyls on its molecular chain, which makes it have a lower surface energy. When beeswax is loaded on the hollow structure, the hydroxyls tend to be exposed outward, so that the entire nanoparticle has a strong hydrophobic property, and the gas filled inside the hollow structure forms a protective layer inside it, which further reduces the contact area between the external substance and the hollow silica. Polydimethylsiloxane is added to tetrahydrofuran, ultrasonically dispersed to completely dissolve it, and then the nano-silica loaded with beeswax is added, and stirring is continued after ultrasonic dispersion to obtain a hydrophobic dispersion, which is fixed on the surface of the material as a hydrophobic layer, which can effectively increase the hydrophobic ability of tableware. DETAILED DESCRIPTION
[0029] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] The following embodiments of the present invention are used:
[0031] The reeds were purchased from the Yunzhi Aquatic Plant Plantation in Majiazhai, Anxin County;
[0032] Toluene was purchased from Chongqing Chuandong Chemical Co., Ltd., CAS No.: 108-88-3;
[0033] Ethanol was purchased from Shandong Mantanghong New Materials Co., Ltd., CAS No.: 64-17-5;
[0034] Potassium hydroxide was purchased from Changzhou Qidi Chemical Co., Ltd., CAS No.: 1310-58-3;
[0035] Potassium permanganate was purchased from Jiangsu Dongcan Chemical Co., Ltd., CAS No.: 7722-64-7;
[0036] Glacial acetic acid was purchased from Nanjing Shengqinghe Chemical Co., Ltd., CAS number: 64-19-7;
[0037] Antioxidant 1010 was purchased from Tianjin Lianlong New Materials Co., Ltd., CAS No.: 6683-19-8;
[0038] Antioxidant 168 was purchased from Shanghai Better Chemical Co., Ltd., CAS No.: 31570-04-4;
[0039] Talc powder was purchased from Liaoning Aihai Talc Co., Ltd., CAS number: 14807-96-6;
[0040] Beeswax was purchased from Shaanxi Tangyao Biotechnology Co., Ltd., CAS number: 8012-89-3;
[0041] Polycaprolactone was purchased from Handan Fuxing District Ao Teng Chemical Trading Co., Ltd., CAS No.: 24980-41-4;
[0042] Cellulose acetate was purchased from Eastman Chemical Company, CAS number: 9004-35-7;
[0043] Pentaerythritol stearate was purchased from Xi'an Xinlu Biotechnology Co., Ltd., CAS No.: 9004-61-9;
[0044] Polydimethylsiloxane was purchased from Shanghai Gonghang Chemical Co., Ltd., CAS number: 58130-04-4;
[0045] Tetrahydrofuran was purchased from Changzhou Youfeng Chemical Co., Ltd., CAS No.: 109-99-9.
[0046] Example 1
[0047] This embodiment discloses a method for preparing modified reed cellulose, comprising the following steps:
[0048] P1: Cut the reed into 5 cm strips, wash and air-dry them naturally, then crush them fully with a cutting grinder, pass them through an 80-mesh sieve to obtain reed powder, take the reed powder and wrap it with filter paper, put it in a Soxhlet extractor, add a mixed solution of toluene and ethanol, the volume ratio of toluene and ethanol is 2:1, extract at 90℃ for 10h, after the extraction is completed, take out the remaining product, vacuum filter, wash, and dry at 105℃ to obtain pretreated reed powder;
[0049] P2: 5 g of pretreated reed powder was placed in a round-bottom flask, and a mixed solution of 55 mL of 4 wt% potassium hydroxide and 45 mL of 0.6 wt% potassium permanganate was added. The round-bottom flask was first ultrasonically cleaned in an ultrasonic cleaner at a frequency of 45 kHz for 30 seconds. The round-bottom flask was then connected to a condensation device and extracted at 80°C for 6 hours. After the extraction was completed, vacuum filtration was performed, the powder was washed until pH = 7, and dried at 105°C to obtain reed crude fiber.
[0050] P3: Place the reed crude fiber in a round-bottom flask, add glacial acetic acid with a pH value of 3.5, place in an 85°C constant temperature oil bath for magnetic stirring, filter, wash, and dry to obtain modified reed cellulose.
[0051] This embodiment discloses a method for preparing nano silicon dioxide loaded with beeswax, comprising the following steps:
[0052] S1: 6.5 mL of tetraethyl orthosilicate was added to a mixed solution of 75 mL of ethanol, 10 mL of deionized water and 3.25 mL of 25 vt% ammonia solution, stirred for 2 h, centrifuged at 5000 rpm, washed, and dried at 130 ° C for 10 h to obtain solid nano-silica particles, then 0.5 g of solid nano-silica particles was ultrasonically dispersed in 90 mL of deionized water, 10 mL of ethanol solution containing 1.25 mL of hexadecyltrimethylammonium bromide was added, stirred for 1 h, 2.15 g of anhydrous sodium carbonate was added, and stirring was continued for 12 h. After heating at 60 ° C and stirring for 20 h, centrifuged, washed, and dried to obtain hollow nano-silica;
[0053] S2: 0.9 g of beeswax was added to 40 mL of ethanol containing 0.4 g of hollow nano-silica, and after ultrasonic dispersion for 40 min, it was placed in a vacuum environment, magnetically stirred for 12 h, washed, and dried to obtain nano-silica loaded with beeswax.
[0054] The present embodiment discloses a cellulose fully biodegradable super-tough tableware, which is composed of a tableware sample embryo and a hydrophobic layer. The tableware sample embryo comprises the following components in parts by weight: 3 parts of polycaprolactone, 80 parts of cellulose acetate, 4 parts of modified reed cellulose, 0.5 parts of pentaerythritol stearate, 10 parts of talc, 0.2 parts of antioxidant 1010, and 0.3 parts of antioxidant 168; the hydrophobic layer comprises the following components in parts by weight: 1 part of nano-silicon dioxide loaded with beeswax, 0.5 parts of polydimethylsiloxane, and 0.5 parts of tetrahydrofuran.
[0055] This embodiment discloses a method for preparing fully biodegradable and ultra-tough cellulose tableware, comprising the following steps:
[0056] Step (1): melt-blending polycaprolactone, cellulose acetate, modified reed cellulose, pentaerythritol stearate, talc, antioxidant 1010, and antioxidant 168 to form granules, then adding the granules into a barrel of an injection molding machine, and injecting the granules into a tableware mold, wherein the melt-blending temperature is 210° C., the injection molding temperature is 220° C., and after cooling, a tableware sample is obtained;
[0057] Step (2): adding polydimethylsiloxane to tetrahydrofuran, dispersing it by ultrasonic for 20 minutes to completely dissolve it, then adding nano-silica loaded with beeswax, dispersing it by ultrasonic for 45 minutes, and then stirring for 30 minutes to obtain a hydrophobic dispersion;
[0058] Step (3): the dispersion is loaded into a spray gun, and the dispersion is evenly sprayed on the surface of the tableware sample at an air pressure of 0.4 MPa. After spraying, the tableware is dried in an oven to obtain fully biodegradable and ultra-tough cellulose tableware.
[0059] Example 2
[0060] This embodiment discloses a method for preparing modified reed cellulose, comprising the following steps:
[0061] P1: Cut the reed into 5 cm strips, wash and air-dry them, then crush them thoroughly with a cutting grinder and pass them through an 80-mesh sieve to obtain reed powder. Wrap the reed powder with filter paper and place it in a Soxhlet extractor. Add a mixed solution of toluene and ethanol in a volume ratio of 2:0.8 and extract at 90°C for 10 h. After the extraction, take out the remaining product, vacuum filter, wash, and dry at 105°C to obtain pretreated reed powder.
[0062] P2: 5 g of pretreated reed powder was placed in a round-bottom flask, and a mixed solution of 50 mL of 4 wt% potassium hydroxide and 40 mL of 0.6 wt% potassium permanganate was added. The round-bottom flask was first ultrasonically cleaned in an ultrasonic cleaner at a frequency of 45 kHz for 30 seconds. The round-bottom flask was then connected to a condensation device and extracted at 80°C for 6 hours. After the extraction was completed, vacuum filtration was performed, the mixture was washed to pH = 7, and dried at 105°C to obtain reed crude fiber.
[0063] P3: Place the reed crude fiber in a round-bottom flask, add glacial acetic acid with a pH value of 3.5, place in an 85°C constant temperature oil bath for magnetic stirring, filter, wash, and dry to obtain modified reed cellulose.
[0064] This embodiment discloses a method for preparing nano silicon dioxide loaded with beeswax, comprising the following steps:
[0065] S1: 5 mL of tetraethyl orthosilicate was added to a mixed solution of 70 mL of ethanol, 8 mL of deionized water and 3 mL of 25 vt% ammonia solution, stirred for 2 h, centrifuged at 5000 rpm, washed, and dried at 130 ° C for 10 h to obtain solid nano-silica particles. Subsequently, 0.3 g of solid nano-silica particles was ultrasonically dispersed in 90 mL of deionized water, and 10 mL of ethanol solution containing 1 mL of hexadecyltrimethylammonium bromide was added. After stirring for 1 h, 2.3 g of anhydrous sodium carbonate was added, and stirring was continued for 12 h. After heating at 60 ° C and stirring for 20 h, the mixture was centrifuged, washed, and dried to obtain hollow nano-silica.
[0066] S2: 0.6 g of beeswax was added to 40 mL of ethanol containing 0.2 g of hollow nano-silica, and after ultrasonic dispersion for 40 min, it was placed in a vacuum environment, magnetically stirred for 12 h, washed, and dried to obtain nano-silica loaded with beeswax.
[0067] The present embodiment discloses a cellulose fully biodegradable super-tough tableware, which is composed of a tableware sample embryo and a hydrophobic layer. The tableware sample embryo comprises the following components in parts by weight: 5 parts of polycaprolactone, 75 parts of cellulose acetate, 8 parts of modified reed cellulose, 1 part of pentaerythritol stearate, 9 parts of talc, 0.1 parts of antioxidant 1010, and 0.2 parts of antioxidant 168; the hydrophobic layer comprises the following components in parts by weight: 1 part of nano-silicon dioxide loaded with beeswax, 0.4 parts of polydimethylsiloxane, and 0.3 parts of tetrahydrofuran.
[0068] The method for preparing fully biodegradable and super-tough cellulose tableware in this embodiment is the same as that in Example 1.
[0069] Example 3
[0070] This embodiment discloses a method for preparing modified reed cellulose, comprising the following steps:
[0071] P1: Cut the reed into 5 cm strips, wash and air-dry them, then crush them thoroughly with a cutting grinder and pass them through an 80-mesh sieve to obtain reed powder. Wrap the reed powder with filter paper and place it in a Soxhlet extractor. Add a mixed solution of toluene and ethanol in a volume ratio of 2:1.2 and extract at 90°C for 10 h. After the extraction is completed, take out the remaining product, vacuum filter, wash, and dry at 105°C to obtain pretreated reed powder.
[0072] P2: 5 g of pretreated reed powder was placed in a round-bottom flask, and a mixed solution of 60 mL of 4 wt% potassium hydroxide and 50 mL of 0.6 wt% potassium permanganate was added. The round-bottom flask was first ultrasonically cleaned in an ultrasonic cleaner at a frequency of 45 kHz for 30 seconds. The round-bottom flask was then connected to a condensation device and extracted at 80°C for 6 hours. After the extraction was completed, vacuum filtration was performed, the mixture was washed to pH = 7, and dried at 105°C to obtain reed crude fiber.
[0073] P3: Place the reed crude fiber in a round-bottom flask, add glacial acetic acid with a pH value of 3.5, place in an 85°C constant temperature oil bath for magnetic stirring, filter, wash, and dry to obtain modified reed cellulose.
[0074] This embodiment discloses a method for preparing nano silicon dioxide loaded with beeswax, comprising the following steps:
[0075] S1: 8 mL of tetraethyl orthosilicate was added to a mixed solution of 80 mL of ethanol, 12 mL of deionized water and 3 mL of 25 vt% ammonia solution, stirred for 2 h, centrifuged at 5000 rpm, washed, and dried at 130 ° C for 10 h to obtain solid nano-silica particles. Subsequently, 0.8 g of solid nano-silica particles was ultrasonically dispersed in 90 mL of deionized water, and 10 mL of ethanol solution containing 1.5 mL of hexadecyltrimethylammonium bromide was added. After stirring for 1 h, 2 g of anhydrous sodium carbonate was added, and stirring was continued for 12 h. After heating at 60 ° C and stirring for 20 h, centrifuged, washed, and dried to obtain hollow nano-silica.
[0076] S2: 1.2 g of beeswax was added to 40 mL of ethanol containing 0.6 g of hollow nano-silica, and after ultrasonic dispersion for 40 min, it was placed in a vacuum environment, magnetically stirred for 12 h, washed, and dried to obtain nano-silica loaded with beeswax.
[0077] The present embodiment discloses a cellulose fully biodegradable super-tough tableware, which is composed of a tableware sample embryo and a hydrophobic layer. The tableware sample embryo comprises the following components in parts by weight: 4 parts of polycaprolactone, 77 parts of cellulose acetate, 8 parts of modified reed cellulose, 0.5 parts of pentaerythritol stearate, 9 parts of talc, 0.2 parts of antioxidant 1010, and 0.2 parts of antioxidant 168; the hydrophobic layer comprises the following components in parts by weight: 0.5 parts of nano-silicon dioxide loaded with beeswax, 0.3 parts of polydimethylsiloxane, and 0.3 parts of tetrahydrofuran.
[0078] The method for preparing fully biodegradable and super-tough cellulose tableware in this embodiment is the same as that in Example 1.
[0079] Example 4
[0080] This embodiment discloses a method for preparing modified reed cellulose, comprising the following steps:
[0081] P1: Cut the reed into 5 cm strips, wash and air-dry them naturally, then crush them fully with a cutting grinder, pass them through an 80-mesh sieve to obtain reed powder, wrap the reed powder with filter paper, put it in a Soxhlet extractor, add a mixed solution of toluene and ethanol, the volume ratio of toluene and ethanol is 2:1.1, extract at 90℃ for 10h, after the extraction is completed, take out the remaining product, vacuum filter, wash, and dry at 105℃ to obtain pretreated reed powder;
[0082] P2: 5 g of pretreated reed powder was placed in a round-bottom flask, and a mixed solution of 58 mL of 4 wt% potassium hydroxide and 43 mL of 0.6 wt% potassium permanganate was added. The round-bottom flask was first ultrasonically cleaned in an ultrasonic cleaner at a frequency of 45 kHz for 30 seconds. The round-bottom flask was then connected to a condensation device and extracted at 80°C for 6 hours. After the extraction was completed, vacuum filtration was performed, the powder was washed until pH = 7, and dried at 105°C to obtain reed crude fiber.
[0083] P3: Place the reed crude fiber in a round-bottom flask, add glacial acetic acid with a pH value of 3.5, place in an 85°C constant temperature oil bath for magnetic stirring, filter, wash, and dry to obtain modified reed cellulose.
[0084] This embodiment discloses a method for preparing nano silicon dioxide loaded with beeswax, comprising the following steps:
[0085] S1: 6 mL of tetraethyl orthosilicate was added to a mixed solution of 78 mL of ethanol, 11 mL of deionized water and 3.4 mL of 25 vt% ammonia solution, stirred for 2 h, centrifuged at 5000 rpm, washed, and dried at 130 ° C for 10 h to obtain solid nano-silica particles, then 0.4 g of solid nano-silica particles was ultrasonically dispersed in 90 mL of deionized water, 10 mL of ethanol solution containing 1.4 mL of hexadecyltrimethylammonium bromide was added, stirred for 1 h, 2.2 g of anhydrous sodium carbonate was added, and stirring was continued for 12 h. After heating at 60 ° C and stirring for 20 h, centrifuged, washed, and dried to obtain hollow nano-silica;
[0086] S2: 0.8 g of beeswax was added to 40 mL of ethanol containing 0.5 g of hollow nano-silica, and after ultrasonic dispersion for 40 min, it was placed in a vacuum environment, magnetically stirred for 12 h, washed, and dried to obtain nano-silica loaded with beeswax.
[0087] The present embodiment discloses a cellulose fully biodegradable super-tough tableware, which is composed of a tableware sample embryo and a hydrophobic layer. The tableware sample embryo comprises the following components in parts by weight: 3 parts of polycaprolactone, 80 parts of cellulose acetate, 5 parts of modified reed cellulose, 0.6 parts of pentaerythritol stearate, 10 parts of talc, 0.1 parts of antioxidant 1010, and 0.2 parts of antioxidant 168; the hydrophobic layer comprises the following components in parts by weight: 0.7 parts of nano-silicon dioxide loaded with beeswax, 0.3 parts of polydimethylsiloxane, and 0.4 parts of tetrahydrofuran.
[0088] The method for preparing fully biodegradable and super-tough cellulose tableware in this embodiment is the same as that in Example 1.
[0089] Comparative Example 1
[0090] Comparative Example 1 Compared with Example 1, in the process of preparing modified reed cellulose in Comparative Example 1, glacial acetic acid was not added, and other conditions remained unchanged.
[0091] Comparative Example 2
[0092] Compared with Example 1, in Comparative Example 2, during the process of preparing the fully biodegradable and super-tough cellulose tableware, no antioxidant 1010 and no antioxidant 168 were added, and other conditions remained unchanged.
[0093] Comparative Example 3
[0094] Compared with Example 1, in Comparative Example 3, during the preparation of the fully biodegradable and super-tough cellulose tableware, no talcum powder was added, and other conditions remained unchanged.
[0095] Comparative Example 4
[0096] Comparative Example 4 Compared with Example 1, in the process of preparing cellulose fully biodegradable and super-tough tableware, no nano-silicon dioxide loaded with beeswax is added in Comparative Example 4, and other conditions remain unchanged.
[0097] Experimental example
[0098] The performance of the cellulose fully biodegradable ultra-tough tableware prepared in Examples 1-4 and Comparative Examples 1-4 was tested. The tableware tested was a cup with a wall thickness of 3 mm, a height of 20 cm, a bottom diameter of 8 cm, and a cylindrical shape.
[0099] The tensile properties of the samples were measured according to GB / T 1040.1-2018, the wetting properties of the samples were measured according to ASTM D724-99, and the degradation properties of the samples were measured according to GB / T 18006.3-2020. The test results are shown in Table 1:
[0100] Table 1
[0101] project Tensile strength / MPa Contact angle / ° Degradation rate / % Example 1 32.83 138.4 ≥90 Example 2 32.17 136.7 ≥90 Example 3 31.14 134.9 ≥90 Example 4 31.52 133.0 ≥90 Comparative Example 1 26.33 132.3 ≥90 Comparative Example 2 26.62 131.2 ≥90 Comparative Example 3 27.31 131.6 ≥90 Comparative Example 4 25.85 112.1 ≥90
[0102] From the test results in Table 1, it can be seen that the super-tough tableware prepared in Examples 1-4 of the present invention has excellent toughness, hydrophobicity and biodegradability. From the comparison between Comparative Example 1 and Examples 1-4, it can be seen that the addition of glacial acetic acid can improve the toughness and thermal stability of the super-tough tableware; from the comparison between Comparative Example 2 and Examples 1-4, it can be seen that the use of antioxidants 1010 and antioxidants 168 can improve the toughness and thermal stability of the super-tough tableware; from the comparison between Comparative Example 3 and Examples 1-4, it can be seen that the addition of talcum powder can effectively improve the toughness and thermal stability of the super-tough tableware; from the comparison between Comparative Example 4 and Examples 1-4, it can be seen that the addition of nano-silica loaded with beeswax can effectively improve the hydrophobicity and toughness of the super-tough tableware.
[0103] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
[0104] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. Cellulose fully biodegradable super tough tableware, characterized by: The tableware sample embryo is composed of a tableware sample embryo and a hydrophobic layer. The tableware sample embryo includes the following components in parts by weight: 3-5 parts of polycaprolactone, 74-80 parts of cellulose acetate, 4-8 parts of modified reed cellulose, 0.5-1.0 parts of pentaerythritol stearate, 9-10 parts of talc, 0.1-0.2 parts of antioxidant 1010, and 0.2-0.3 parts of antioxidant 168; the hydrophobic layer includes the following components in parts by weight: 0.5-1 parts of nano silicon dioxide loaded with beeswax, 0.25-0.5 parts of polydimethylsiloxane, and 0.25-0.5 parts of tetrahydrofuran.
2. The cellulose fully biodegradable super-tough tableware according to claim 1, characterized in that: The method for preparing the modified reed cellulose comprises the following steps: P1: Cut the reed into long strips, wash and air-dry them naturally, then fully crush them with a cutting grinder, sieve them to obtain reed powder, take the reed powder and wrap it with filter paper, put it in a Soxhlet extractor, add a mixed solution of toluene and ethanol, heat and extract, after the extraction is completed, take out the remaining product, vacuum filter, wash and dry it to obtain pretreated reed powder; P2: The pretreated reed powder is placed in a round-bottom flask, and a mixed solution of potassium hydroxide and potassium permanganate is added. The round-bottom flask is first ultrasonically cleaned in an ultrasonic cleaner, and then the round-bottom flask is connected to a condensation device for extraction. After the extraction is completed, vacuum filtration, washing, and drying are performed to obtain reed crude fiber; P3: Place the reed crude fiber in a round-bottom flask, add glacial acetic acid, place it in a constant temperature oil bath for magnetic stirring, filter, wash, and dry to obtain modified reed cellulose.
3. The cellulose fully biodegradable super-tough tableware according to claim 2, characterized in that: In the P1, the length of the strip is 3-5 cm, the sieved particle size is 80-100 mesh, the volume ratio of toluene to ethanol is 2: (0.8-1.2), the heating temperature is 80-90°C, the extraction time is 8-10h, and the drying temperature is 100-105°C.
4. The cellulose fully biodegradable super-tough tableware according to claim 2, characterized in that: In the P2, the dosage ratio of reed powder, potassium hydroxide and potassium permanganate is 5g: (50-60) mL: (40-50) mL, the mass fraction of potassium hydroxide is 4wt%, and the volume fraction of potassium permanganate is 0.6vt%. During the ultrasonic cleaning process, the ultrasonic frequency is 45-50kHz, the cleaning time is 20-40s, the extraction treatment temperature is 70-80°C, the extraction treatment time is 4-6h, the washing is carried out until the pH value is 7, and the drying temperature is 100-110°C. In the P3, the pH value of glacial acetic acid is 3.5, and the temperature of the constant temperature oil bath pot is 80-90°C.
5. The cellulose fully biodegradable super-tough tableware according to claim 1, characterized in that: The method for preparing the beeswax-loaded nano-silicon dioxide comprises the following steps: S1: adding tetraethyl orthosilicate to a mixed solution of ethanol, deionized water and ammonia solution, stirring, centrifuging, washing and drying to obtain solid nano-silica particles, then ultrasonically dispersing the solid nano-silica particles in deionized water, adding an ethanol solution containing hexadecyltrimethylammonium bromide, stirring and adding anhydrous sodium carbonate, continuing to stir, heating and stirring, centrifuging, washing and drying to obtain hollow nano-silica; S2: beeswax is added to ethanol containing hollow nano-silica, and after ultrasonic dispersion, it is placed in a vacuum environment, magnetically stirred, washed, and dried to obtain nano-silica loaded with beeswax.
6. The cellulose fully biodegradable super-tough tableware according to claim 5, characterized in that: In the S1, the volume ratio of tetraethyl orthosilicate, ethanol, deionized water and ammonia solution is (5-8): (70-80): (8-12): (3-3.5), the volume fraction of ammonia solution is 25vt%, the stirring time is 1-2h, the centrifugal speed is 4000-5000rpm, the drying temperature is 120-130°C, the drying time is 10-12h, and the amount ratio of solid nano-silicon dioxide particles, deionized water, hexadecyltrimethylammonium bromide, ethanol and anhydrous sodium carbonate is (0.3-0.8) g: 90 mL: (1-1.5) g: 10 mL: (2-2.3) g, stirring time is 1-2 h, continued stirring time is 10-12 h, heating temperature is 50-60 ° C, stirring time is 20-22 h; in S2, the amount ratio of beeswax, hollow nano-silica and ethanol is (0.6-1.2) g: (0.2-0.6) g: 40 mL, ultrasonic dispersion time is 30-40 min, and magnetic stirring time is 12-14 h.
7. The method for preparing the fully biodegradable and ultra-tough cellulose tableware according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step (1): melt-blending and granulating polycaprolactone, cellulose acetate, modified reed cellulose, pentaerythritol stearate, talc, antioxidant 1010, and antioxidant 168, then adding the mixture into a barrel of an injection molding machine, and injecting the mixture into a tableware mold, and cooling the mixture to obtain a tableware sample embryo; Step (2): adding polydimethylsiloxane to tetrahydrofuran, dispersing it by ultrasonication to make it completely dissolved, then adding nano-silica loaded with beeswax, dispersing it by ultrasonication and continuing to stir to obtain a hydrophobic dispersion; Step (3): The dispersion is loaded into a spray gun and sprayed evenly on the surface of the tableware sample. After the spraying is completed, the tableware sample is placed in an oven for curing to obtain cellulose fully biodegradable and ultra-tough tableware.
8. The method for preparing the fully biodegradable and ultra-tough cellulose tableware according to claim 7, characterized in that: In the step (1), the melt blending temperature is 210°C-230°C, and the injection molding temperature is 210°C-230°C.
9. The method for preparing the fully biodegradable and ultra-tough cellulose tableware according to claim 7, characterized in that: In the step (2), the ultrasonic dispersion time is 15-20 min, the ultrasonic dispersion time after adding the nano-silica loaded with beeswax is 30-45 min, and the stirring time is 30-40 min; in the step (3), the air pressure of the spray gun is 0.2-0.4 MPa, and the mixture is dried in a drying room.